Estatísticas culturais no Nordeste : cultura popular e políticas públicas de desenvolvimento. - Azevedo, Luciane Dias de (2010)
This work investigates the hypothesis although culture in the Northeast region lacks access and market of industrialized products and services - especially in what concerns cultural infrastructure - represents a remarkable cultural diversity when compared to other Brazilian regions in popular culture expressions. This hypothesis allow us to also make a significant relation between the reality presented in Northeast culture statistics and regional cultural public policies, especially when it comes to financing programs, such as Lei Rouanet . We realize that this cultural diversity is not followed by public investment in culture, still highly concentrated in Brazilian Southeast. All numbers and data were extracted from the Anuário de Estatísticas Culturais 2009 , published by the Ministry of Culture. Our work includes the main statistic researches of the Federal Government since 2004, period in which there is a higher amount of information produced about culture. The importance of this subject concerns the role of culture as a tool for socioeconomic development in regions, nations and the world, as we can see in the relevant participation of this sector in national economies, whether in the generation of jobs and incomes or in a better quality of life in communities as a whole. Culture and development over the last decade has also been a theme strongly present in the discussions of internationally recognized institutions such as UNO (United Nations Organization).